Response to Letter to the Editor - Folashayo Adeniji; Taiwo Obembe (Journal of Health Economics and Outcomes Research)
The authors respond to the comments raised in the letter regarding Adeniji and Obembe's article on catastrophic health expenditures in sub-Saharan Africa.